Spork - Maclear, Kyo, 1970- (Kids Can Press, 2010)
His mum is a spoon, his dad is a fork, and he's a bit of both: he's Spork, a utensil who just doesn't seem to fit into the regimented world of the cutlery drawer, and this is his "multi-cutlery" tale, a humorous commentary on individuality and tolerance, that capture the experience and emotions of all who have ever wondered about their place in the world.